Complex preparation of patients with recurrent implantation failure for the transfer of good quality embryos in ivf-et cycles - Nosenko, O.; Demidchik, R. (Journal of Education, Health and Sport, 2024)
The purpose of the study is to evaluate the effectiveness of the proposed method of complex preparation of patients with RIF with the restoration of the profile of vaginal microbiota and the functions of the main systems of sanogenesis with the help of adjuvants before the next attempt to transfer vitrified / warmed embryos of good quality in segmented IVF-ET cycles. Material and methods. 68 women of reproductive age with infertility and RIF, who were repeatedly but unsuccessfully treated in IVF-ET cycles with transfer of good quality embryos, and 32 fertile control women were comprehensively examined. A method of preparing patients with RIF for IVF-ET was developed, which included extended profiling of the vaginal microbiome, combined use of oral and vaginal antibacterial drugs against the background of the use of enzyme agents and antibiotic-resistant probiotics, as well as progestogens, melatonin, vitamin D, adjuvants for the correction of oxidative, nitrosative stress and restoration of endothelial function. The patients of the group with RNI were divided into 2 groups: 35 women who were prepared for the next attempt of IVF-ET according to the proposed method, and 33 patients who received the standard method of preparation. The microbiological, laboratory and clinical results of the training were evaluated. The results. Improvement of the composition of the vaginal microbiota, hormonal, nitrosative and oxidative status, functional activity of the endothelium of patients with RIF according to the proposed method of preparation for IVF-ET led to an increase in the frequency of clinical pregnancy by 2.26 times (45.71% vs. 21.21 %; OR 3.1278 [95% CI 1.0759-9.0930], p<0.04) and termination of induced pregnancy by delivery 3.30 times (40.00 % vs. 12.12 %; OR 4.8333 [95% CI 1.3916-16.7870], p<0.02). Conclusions. The proposed complex method of preparing patients with RIF before IVF-ET is effective and can be recommended for use in clinical practice.